THE INFLUENCE OF CONTENT MARKETING, SOCIAL MEDIA MARKETING, AND BRAND AWARENESS ON GEN-Z BUYING DECISIONS AT SHOPEE - SYAKDIYAH, FIRA HIDAYATUS; Bhirawa, Sigit Wisnu Setya (Universitas Nusantara PGRI Kediri, 2025)
Research aim: The purpose of this study is to determine whether there is a significant partial and simultaneous influence between the variables of Content Marketing, Social Media Marketing, and Brand Awareness on Gen-Z Buying Decisions at Shopee for Management Students of Class 2021, UNP Kediri. Design/Method/Approach: This study uses a quantitative causality approach. The population of this study is management students of Class 2021, the sampling uses probability sampling with a simple random sampling technique, the number of samples is 80 respondents, data analysis uses classical assumption tests, multiple linear regression equations, determination coefficient tests, and hypothesis tests with SPSS 25 tools. Research Finding: The findings of this study indicate that there is a positive and significant influence of the content marketing and brand awareness variables on buying decisions, but there is no significant influence on the social media marketing variable on buying decisions. And there is a significant influence of the three variables simultaneously on buying decisions. Theoretical contribution/Originality: This study contributes to the digital marketing literature by highlighting how the combination of content marketing, social media marketing, and brand awareness variables influences buying decisions, especially for Gen-Z on the Shopee platform. Practitioner/Policy implication: These findings can be used as a guide for marketers on Shopee to improve the effectiveness of their digital strategies in attracting Gen-Z interest through optimizing content marketing, social media marketing, and increasing brand awareness. Research limitation: This study is limited to management students of the 2021 UNP Kediri Class Keywords: Content Marketing, Social Media Marketing, Brand Awareness, Buying Decision.